Medicolegal Online-Based Medical Records In Improving Health Services - Ratu Taga, Christiana Diana (Asian Journal of Social and Humanities, 2023)
The hospital is one of the health care facilities that organizes various health services. One of the supporting units of health services is medical records. The presence of technology also makes changes to medical records from manual to online-based or what is commonly referred to as electronic medical records. This study aims to determine the improvement of health services through online-based medical record medicolegal. This research method uses the documentation method with a qualitative approach. The data collection technique is the literature review technique. Then the data is analyzed referring to Miles & Huberman in going through the stages of data reduction, data display, conclusion drawing/verification. The results showed that online-based medicolegal medical records or electronic medical records can improve health services because medical records have several advantages over manual medical records including increasing productivity, being more efficient, it is very easy to issue patient medical records both in recap and detail, and doctors and nurses can easily access patient data